Data: Effect of machine hammer peening conditions on β grain refinement of additively manufactured Ti-6Al-4V - Machado Santos Carvalho Neto, Leonor; Williams, Stewart W.; Davis, Alec E.; Kennedy, Jacob (Cranfield University, 2023)
The data in this folder is a table with the average grain size according to variations of parameters studied. This information is given in the paper as a graphical representation and is here described to support any further studies.
Keywords: Machine Hammer Peening; Wire arc additive manufacturing (WAAM); microstructure; grain refinement; Mechanical properties; titanium alloys